Pengaruh Manajemen Mutu ISO 9001:2015 dan Motivasi Kerja Terhadap Kinerja Karyawan Studi Kasus PT Waskita Swadiri Nirbaya Unit Kerja Pantai Indah Kapuk (PIK) - Billy Frany Mawikere; Elmira Siska (Ebisnis Manajemen, 2025)
PT Waskita Swadiri Nirbaya is a company engaged in the Security Services (Satpam) sector. Issues related to quality management arise as some employees feel that the implementation of quality management in the company does not fully support their work effectiveness, resulting in reduced motivation to perform their tasks optimally. The purpose of this study is to analyze the influence of quality management and work motivation, both partially and simultaneously, on employee performance at PT Waskita Swadiri Nirbaya. The research method employs a quantitative design. Sampling was conducted using a saturated sampling technique with 50 employees. Data processing methods include data quality testing, consisting of validity and reliability tests, classical assumption tests, t-tests, and F-tests. The study results show that the questionnaire variables are valid, reliable, and free from econometric issues. The quality management variable has a positive and significant partial influence on employee performance at PT Waskita Swadiri Nirbaya. Similarly, the work motivation variable has a positive and significant partial influence on employee performance. Simultaneously, both variables positively and significantly influence employee performance at PT Waskita Swadiri Nirbaya. The findings of this study can serve as a foundation for developing broader human resource management strategies by incorporating quality management and motivation aspects as key elements in improving employee performance.